Glowinski and numerical control problems - Fernández-Cara, Enrique (Comptes Rendus. Mécanique)
This paper is devoted to recall several contributions to the numerical control of PDE’s that have origin in Glowinski’s work. I will consider null controllability problems for linear and nonlinear heat equations and some free-boundary systems. We will also deal with some bi-objective optimal control problems. Additionally, some new methods and results will be announced.